THE IMPACTS OF BANK FINANCIAL SOUNDNESS TOWARDS PROFIT GROWTH: A STUDY ON THE INDONESIAN BANKING INDUSTRY - Theresia Lesmana, Dezie L. Warganegara , Rita Trifena (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This research aims to analyze the effect of bank performance on profit growth using RGEC (Risk Profile, GCG, Earnings, and Capital) approach. Risk Profile is measured with NPL and LDR. GCG is assessed with the self-assessment review based on 11 (eleven) assessment factors. Earnings are measured by OER and ROA, and Capital is measured by CAR. The results of this study can be summarized into six independent variables, there are two significant independent variables and four not significant independent variables in explaining the variations in profit growth. The significant are ROA and CAR. The not significant ones are NPL, LDR, GCG, and OER.